1. The problem statement, all variables and given/known data Consider: y = f(x) = ax^2+bx+c, where a, b and c are real constants. Prove that y*=f(x*) 2. Relevant equations conjugate of a complex number x=a+jb and x*=a-jb 3. The attempt at a solution You can show the answer of f(x*) by substituting (a-jb) for each x in f(x), but I was confused on how you do the conjugate of an entire function. Would you try to find the roots of y and f(x*) each and then take the conjugate roots of y, and if they are the same then y*= f(x*)?